Combinatorial Resource Allocation in UAV-Assisted 5G/B5G Heterogeneous Networks - Shahzadi, Rizwana; Ali, Mudassar; Naeem, Muhammad (IEEE access, 2023)
The advancements in technology have greatly influenced our daily lives and have brought about numerous changes in the way we live, work, and communicate. The rise of social media platforms has resulted in the transformation of the ways people interact and share information. Therefore existing terrestrial infrastructure needs to be replaced by modern communication means. Unmanned aerial vehicles (UAVs) have proved their potential to play a significant role in heterogeneous networks (HetNets) by providing additional coverage and capacity in areas that are crowded or hit by any natural disaster due to several associated advantages. This work has presented an optimized resource allocation problem in UAV-assisted HetNet. An outer approximation(OAA) based novel algorithm has been proposed to solve the presented mixed integer nonlinear programming problem (MINLP). Complexity Comparison of the proposed algorithm with other state-of-the-art methods is presented. The Prime objective is to maximize the network data rate subject to the constraints of power and Quality of service (QoS). Extensive simulation work is performed to compare the UAV-assisted HetNet data rate and associated users with Macro-only scenarios. Results have proved the outperformance of the proposed algorithm. UAV-assisted HetNet data rate and associated users are also investigated for different Quality of service (QoS) requirements and results have proved that the proposed OAA algorithm has still maintained its outperformance as compared to conventional HetNets. The result Section also includes the simulation results of the comparison between the proposed OAA-based algorithm with other state-of-the-art methods.